HUBUNGAN ANTARA JENIS PERSALINAN DENGAN KEBERHASILAN ASI EKSKLUSIF DI KECAMATAN BAKI KABUPATEN SUKOHARJO - Warsini Warsini; Sri Aminingsih; Rizky Ayu Fahrunnisa (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background Results of Indonesia Demographic and Health Survey (IDHS) in 2012 showed coverage exclusive breastfeeding in Indonesia have not been optimal, that was 42 %. This study was conducted to analyze the correlation between the kinds of giving births with the success of exclusive breastfeeding 6 (six) months.The subject and Methods The study was a quantitative analytic observational cross-sectional design. Large samples are 100 mothers  who had babies aged 6-12 months. Sampling random sampling. Collecting data using questionnaires.The results showed that the average maternal age 20-35 years (80%), birth weight children mostly above 2,500 g (97%), maternal gestational age infants mostly pretty months (99%) and all infants the respondent was not born with congenital abnormalities, meaning that 100% of infants born with a normal weight difference, kinds of giving birth the mean of paravaginal (70%), the success rate of exclusive breastfeeding by 56%. Statistical shows that there is a positive correlation and statistically significant between the kinds of giving births with the success of exclusive breastfeeding (OR = 2.53 ; CI 95% 1.05 until 6.10 ; p = 0.035).Conclusion There was a significant correlation between the kinds of giving births with the success of exclusive breastfeeding.Keywords: the kinds of giving births, exclusive breastfeeding